2018
DOI: 10.1002/ajhb.23154
|View full text |Cite
|
Sign up to set email alerts
|

When women work: Endocrine reactivity in women during everyday physical activity at high altitude

Abstract: Testosterone and cortisol increase allocation of energy to costly somatic tissues and the utilization of stored energy. Lower production of these hormones may be beneficial for heightened energetic demands at high altitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Furthermore, research recently reported that females from the same valley had decreased levels of cortisol and testosterone. These two hormones increase somatic costs and utilization of stored energy; reducing their levels could be an adaptive response to the high energy demands of living in a high-altitude environment (Sarma et al 2018).…”
Section: High-altitude Acclimatizationsmentioning
confidence: 99%
“…Furthermore, research recently reported that females from the same valley had decreased levels of cortisol and testosterone. These two hormones increase somatic costs and utilization of stored energy; reducing their levels could be an adaptive response to the high energy demands of living in a high-altitude environment (Sarma et al 2018).…”
Section: High-altitude Acclimatizationsmentioning
confidence: 99%
“…Elsewhere, research on adaptive responses in geographic extremes presented novel evidence that hormonal responses to physical activity may vary at high altitude (Sarma et al. ), and that supraclavicular brown adipose tissue in Yakut adults (Siberia) may play a role in nonshivering thermogenesis and, therefore, cold adaptation in this population (Levy et al. ).…”
Section: Contextual Variation In Biology and Behaviormentioning
confidence: 99%